2018
DOI: 10.7567/jjap.57.025602
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of femtosecond-laser-induced periodic structures on SiC substrates

Abstract: We investigated the crystalline state of femtosecond-laser-induced periodic structures using a transmission electron microscope (TEM). The core of the 200-nm-pitch periodic nanostructures on SiC retained a high crystalline quality continued from the SiC substrate, where the crystal orientation was aligned with that of the SiC substrate. These results suggest that the periodic nanostructures were formed by periodic etching and not by rearrangement. At high laser power, microstructures with sizes larger than 2 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Further details are actively under discussion. Research regarding the crystal state of LIPSS still continues, [7][8][9][10] and we have previously reported that it depends on the irradiated material. 7) Previous published literature shows that the period of LIPSS changes depending on a number of factors including, the number of superimposed laser pulses, 11,12) laser energy fluence, 4,13,14) laser scanning rate, 15) laser wavelength, 14,[16][17][18][19] and irradiated material.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further details are actively under discussion. Research regarding the crystal state of LIPSS still continues, [7][8][9][10] and we have previously reported that it depends on the irradiated material. 7) Previous published literature shows that the period of LIPSS changes depending on a number of factors including, the number of superimposed laser pulses, 11,12) laser energy fluence, 4,13,14) laser scanning rate, 15) laser wavelength, 14,[16][17][18][19] and irradiated material.…”
mentioning
confidence: 99%
“…Research regarding the crystal state of LIPSS still continues, [7][8][9][10] and we have previously reported that it depends on the irradiated material. 7) Previous published literature shows that the period of LIPSS changes depending on a number of factors including, the number of superimposed laser pulses, 11,12) laser energy fluence, 4,13,14) laser scanning rate, 15) laser wavelength, 14,[16][17][18][19] and irradiated material. 20) As these results showed, the period of LIPSS can be controlled by laser parameters, mainly the laser wavelength; however, the range and controllability obtained through this method are not enough for the desired control level.…”
mentioning
confidence: 99%
“…Therefore, it has been chosen as the substrate for the samples used in this study. We investigated the crystallinity of the LIPSS by Synchrotron high-energy x-ray diffraction (XRD), through a correlation with crystallographic analysis of transmission electron microscope (TEM) observation [38][39][40][41] .…”
mentioning
confidence: 99%
“…The rapid development and widespread application of femtosecond (fs) laser with the additional advantages of high peak fluence and minimal thermal effect have opened a new avenue in micro-/nano-processing, which is especially important for wide bandgap and transparent materials. 1,2) The irradiation of solids with linearly-polarized fs laser has been known to result in the formation of laser-induced periodic surface structures (fs-LIPSS), also known as ripples, [3][4][5] which have been observed extensively in metals 6,7) and semiconductors, [8][9][10][11][12] with multifarious irradiation conditions. Due to the novel electronic, optical, and mechanical properties, the fs-LIPSS have broadened the potential applications in the high-tech industry.…”
mentioning
confidence: 99%